IMRT delivers lower radiation doses to dental structures than 3DRT in head and neck cancer patients - Fregnani, Eduardo Rodrigues (Radiat Oncol, 2016)
BACKGROUND: Radiotherapy (RT) is frequently used in the treatment of head and neck cancer, but different side-effects are frequently reported, including a higher frequency of radiation-related caries, what may be consequence of direct radiation to dental tissue. The intensity-modulated radiotherapy (IMRT) was developed to improve tumor control and decrease patient’s morbidity by delivering radiation beams only to tumor shapes and sparing normal tissue. However, teeth are usually not included in IMRT plannings and the real efficacy of IMRT in the dental context has not been addressed. Therefore, the aim of this study is to assess whether IMRT delivers lower radiation doses to dental structures than conformal 3D radiotherapy (3DRT). MATERIAL AND METHODS: Radiation dose delivery to dental structures of 80 patients treated for head and neck cancers (oral cavity, tongue, nasopharynx and oropharynx) with IMRT (40 patients) and 3DRT (40 patients) were assessed by individually contouring tooth crowns on patients’ treatment plans. Clinicopathological data were retrieved from patients’ medical files. RESULTS: The average dose of radiation to teeth delivered by IMRT was significantly lower than with 3DRT (p = 0.007); however, only patients affected by nasopharynx and oral cavity cancers demonstrated significantly lower doses with IMRT (p = 0.012 and p = 0.011, respectively). Molars received more radiation with both 3DRT and IMRT, but the latter delivered significantly lower radiation in this group of teeth (p < 0.001), whereas no significant difference was found for the other dental groups. Maxillary teeth received lower doses than mandibular teeth, but only IMRT delivered significantly lower doses (p = 0.011 and p = 0.003). Ipsilateral teeth received higher doses than contralateral teeth with both techniques and IMRT delivered significantly lower radiation than 3DRT for contralateral dental structures (p < 0.001). CONCLUSION: IMRT delivered lower radiation doses to teeth than 3DRT, but only for some groups of patients and teeth, suggesting that this decrease was more likely due to the protection of other high risk organs, and was not enough to remove teeth from the zone of high risk for radiogenic disturbance (>30Gy).